The Role of Budgetary Participation and Environmental Uncertainty in Influencing Managerial Performance of Village Government - Hafiez Sofyani; Muhamad Fandi Indra Santo Simali; Taufik Najda; Mohammed Saleh Al-Maghrebi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: This study aims to examine the influence of budgetary participation and environmental uncertainty on the managerial performance of the village government. In addition, it examines the budgetary participation as an intervening variable.Design/Methodology/Approach: The research was conducted using a survey method by distributing questionnaires to village governments in Bantul Regency, Indonesia. Totally, 118 completed questionnaires were returned. Data analysis was carried out using a partial least squares (PLS) approach.Research findings: The results revealed that budgetary participation and environmental uncertainty significantly influenced managerial performance. Besides, environmental uncertainty was found as a determinant of budgetary participation implementation. This study confirmed that budgetary participation had an intervening role in the environmental uncertainty-managerial performance relationship.Theoretical contribution/ Originality: This research pioneered the testing of budgetary participation as the intervening variable in the context of a village government study.Practitioner/Policy implication: Referring to the results, the village government needs to appreciate the practice of budgetary participation to encourage managerial performance, especially to convert the negative impact of environmental uncertainty to be a chance to achieve better performance.Research limitation/Implication: This research was only undertaken in the scope of Bantul regency. Therefore, the generalization ability of this study is limited.